1995
DOI: 10.3758/bf03206801
|View full text |Cite
|
Sign up to set email alerts
|

Within-category discrimination of musical chords: Perceptual magnet or anchor?

Abstract: Recent speech research has begun to evaluate the internal structure of categories. In one such study, Kuhl (1991) found that discrimination was poorer for vowel stimuli that were more representative of the category (prototype, or P, set) than it was for less representative stimuli (nonprototype, or Np, set). This finding was interpreted as indicating that a category prototype may function as a "perceptual magnet," effectively decreasing perceptual distance, and thus discriminability, between stimuli. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This phenomenon is consistent with previous studies of categorical perception that examined within-category changes. Once a subjective category has been formed, changes in toward the prototype of the category are less detectable than changes toward the boundaries ( Etcoff and Magee, 1992 ; Acker et al, 1995 ). Further, a recent study on the sense of control also reported that initial exploration of control greatly influences the detection sensitivity of changes in the subsequent sensing of control ( Wen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is consistent with previous studies of categorical perception that examined within-category changes. Once a subjective category has been formed, changes in toward the prototype of the category are less detectable than changes toward the boundaries ( Etcoff and Magee, 1992 ; Acker et al, 1995 ). Further, a recent study on the sense of control also reported that initial exploration of control greatly influences the detection sensitivity of changes in the subsequent sensing of control ( Wen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The suggested attraction effect is in line with the assimilation to prototypes or perceptual magnet hypothesis , which states that reference points shrink the psychological distance around them, which implies decreased sensitivity around reference points (Feldman et al, 2009; Hellström, 2007; Kuhl, 1991; Samuel, 1982). In contrast, the perceptual anchor hypothesis suggests that reference points (i.e., anchors) cause an increase in sensitivity in their vicinity (Acker et al, 1995; Quinn, 2000). Evidence has been found for both of these hypotheses, and task context seems to be a moderating factor (Quinn, 2000), whereas increased sensitivity around reference points (above threshold) has been found for tasks involving direct perceptual comparisons with plenty of perceptual evidence present and minimal memory demands, decreased sensitivity around reference points has been reported for tasks in which a currently available stimulus was compared to stimuli stored in memory (i.e., for which there was limited perceptual input).…”
Section: Categorization and The Category Boundary Effectmentioning
confidence: 96%
“…A musical prototype can assimilate an area of approximately 25 cents in either direction (Vurma & Ross, 2006), i.e., musically trained listeners may perceive all stimuli within 25 cents of a prototype to be identical (Perlman & Krumhansl, 1996;Siegel & Siegel, 1977a). Alternatively, a prototype may show enhanced discrimination in its immediate vicinity compared to the same area surrounding a non-prototype (Acker, Pastore, & Hall, 1995;McFadden & Callaway, 1999). Neither of these effects must necessarily occur, even among trained listeners (Schellenberg, 2002); however, it may be that with increasing musical experience, a prototype gradually changes from magnet to anchor, as detecting fine mistunings becomes more important to professional performance (Barrett, 1999).…”
Section: Prototype Effectsmentioning
confidence: 99%